1995
DOI: 10.1063/1.1145919
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a soft x-ray quadruple reflection circular polarizer

Abstract: We built a quadruple reflection polarizer which can be used in the energy range hν=8–130 eV to convert linearly polarized synchrotron radiation into circularly polarized light of either left or right handedness. The design permits independent adjustment of the angle of reflection θ as well as the angle of rotation α along the light axis. These adjustments allow us to operate the polarizer at any given energy in a mode where either the degree of circular polarization Pcirc or the figure of merit TP2circ is maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Further details about the design and optical performance of the QRP are reported elsewhere. 23,24 Thin Fe films were deposited in vacuum on a nonmagnetic substrate using a molecular-beam-epitaxy effusion cell. The films were magnetized in longitudinal or polar orientations by rare-earth permanent magnets mounted on the sample holder.…”
Section: Methodsmentioning
confidence: 99%
“…Further details about the design and optical performance of the QRP are reported elsewhere. 23,24 Thin Fe films were deposited in vacuum on a nonmagnetic substrate using a molecular-beam-epitaxy effusion cell. The films were magnetized in longitudinal or polar orientations by rare-earth permanent magnets mounted on the sample holder.…”
Section: Methodsmentioning
confidence: 99%
“…Verification of the proper operation of the QRP and its utility in MCD measurements can be found elsewhere. 17,18 Thin Fe films were grown under ultrahigh-vacuum conditions and at room temperature on Si͑100͒ substrates using an electron-beam evaporator, and film thickness was monitored with a quartz microbalance. To prevent reaction and interdiffusion between the Fe films and Si substrates, a 200-Å layer of Cu was first deposited.…”
Section: Methodsmentioning
confidence: 99%
“…Independently, Westerveld et al (1985) developed the theory for conversion of linear-to-circular polarization using reflections optics and demonstrated the feasibility of this approach with an apparatus in which linearly polarized light was reflected from a single gold mirror. Koida et al (1991a,b) achieved approximately 82% circular polarization with a triple-reflection device designed to operate over the spectral range from 5 to 30 eV (250 to 41 nm), while Hochst et al (1994) have proposed and tested (Hochst et al, 1995) a quadruple reflection device to span the range of 8 to 100 eV (155 to 12.4 nm) and Suzuki et al (1995) have reported a four-reflection device and demonstrated that it can generate circularly polarized light from 14 to 25 eV and nearly circularly polarized light to 40 eV. Smith and Howells (1994) have proposed that circular polarization can be achieved over a narrower spectral range but with higher throughput than the three-and four-reflection devices by using large numbers of grazing incidence reflections, i.e., "whispering galleries.…”
Section: Phase-shiftersmentioning
confidence: 98%